2019
DOI: 10.1242/jcs.231373
|View full text |Cite
|
Sign up to set email alerts
|

Chromogranin B regulates early-stage insulin granule trafficking from the Golgi in pancreatic islet β-cells

Abstract: Chromogranin B (CgB, also known as CHGB) is abundantly expressed in dense core secretory granules of multiple endocrine tissues and has been suggested to regulate granule biogenesis in some cell types, including the pancreatic islet β-cell, though the mechanisms are poorly understood. Here, we demonstrate a critical role for CgB in regulating secretory granule trafficking in the β-cell. Loss of CgB impairs glucosestimulated insulin secretion, impedes proinsulin processing to yield increased proinsulin content,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(96 citation statements)
references
References 50 publications
4
88
0
Order By: Relevance
“…Numerous proteins of importance for proinsulin condensation have been identified, including chromogranin A (CHGA), chromogranin B (CHGB) and VGF. Mice lacking CHGB exhibit reduced glucose-stimulated insulin secretion, and similar defects are seen in islets and clonal β-cells following transient knockdown of CHGB [ 12 , 13 ]. Mechanistically, loss of CHGB does not affect ISG biogenesis but it impairs proinsulin processing, leading to reduced insulin content [ 12 ].…”
Section: Trans- Golgi Network Sorting Of Proinsulin and Formmentioning
confidence: 99%
“…Numerous proteins of importance for proinsulin condensation have been identified, including chromogranin A (CHGA), chromogranin B (CHGB) and VGF. Mice lacking CHGB exhibit reduced glucose-stimulated insulin secretion, and similar defects are seen in islets and clonal β-cells following transient knockdown of CHGB [ 12 , 13 ]. Mechanistically, loss of CHGB does not affect ISG biogenesis but it impairs proinsulin processing, leading to reduced insulin content [ 12 ].…”
Section: Trans- Golgi Network Sorting Of Proinsulin and Formmentioning
confidence: 99%
“…Furthermore, the biogenesis of DCVs are under the control of Chromogranin B (CHGB) [66], which also exhibited increased gene expression in the adrenal and pancreatic tissues of the KK/ HlJ mice. Recent studies have shown that siRNAtargeted loss of CHGB in vitro impairs glucosestimulated insulin secretion and reduces the density of insulin-containing granules [67]. Additionally, in the adrenal gland loss of CHGB in knockout mice was shown to reduce chromaffin granule abundance by approximately 35% which promoted deregulation of catecholamine release; whereas lentiviral over-expression led to a greater abundance of DCVs [68], suggesting a key role for CHGB and PTPRN in endocrine secretion.…”
Section: Discussionmentioning
confidence: 99%
“…CgB derives from numerous neurons, endocrine and neuroendocrine cell types throughout the human body [ 1 ]. CgB contributes to the physiological secretion of insulin in pancreatic beta cells [ 9 11 ], moreover, it may take part in the signal transduction of insulin secretion [ 19 ]. Furthermore, the messenger RNA quantity of CgB is reduced in pancreatic islets of type 2 diabetes patients than that of non-diabetic control subjects [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chromogranins are associated with the carbohydrate metabolism: CgA is known to play a significant role in the development and pathogenesis [ 5 7 ] of type 1 diabetes and it is associated with some type 1 diabetes complications, which could develop into neuroendocrine tumors [ 8 ]. Animal and cellular models have shown that CgB is mostly related to the physiological insulin secretion [ 9 11 ], however, human clinical study investigating the connection between CgB and diabetes has not been conducted yet.…”
Section: Introductionmentioning
confidence: 99%